Perspective of School Assessment in the Curriculum through the Eyes of the Administrative and Teaching Stakeholders in Nigeria (2020)
This chapter focuses on tools useful in the assessment of cognitive domain of learning. The procedures for constructing and using continuous assessment, paper-pencil test, quizzes, open note test, .computer-based testing, formative assessment, summative assessment, school based assessment, project based assessment, presentations assessment, journals assessment, thought process assessment, resiliency assessment, ability to work in a group assessment, fulfilling requirement assessment, questionnaire assessment and survey assessment are discussed. The chapter also discusses the advantages and limitations of the assessment tools in the teaching learning process. Keywords: perspective, assessment, curriculum, administrative, teaching, stakeholders